Peluang Industri Pertanian Komoditas Kopi (Coffe) Di Kecamatan Seponti Kabupaten Kayong Utara Desa Sungai Sepeti - Martanto, Martanto; Nur Aisyah, Devi; Indriawan, Rois (Jurnal Teknologi Pangan dan Industri Perkebunan (LIPIDA), 2024)
The coffee industry in Indonesia has a strategic role in the national economy, contributing as a source of income for millions of farmers. With production reaching 794.8 thousand tons in 2022, Indonesia is one of the largest coffee producing countries in the world. This study examines the opportunities of the coffee commodity farming industry in Sponti District, North Kayong Regency, which has great potential thanks to favorable agro-climatic conditions and superior coffee varieties. Growing global demand, driven by a growing middle class in developing countries, creates vast market opportunities. However, challenges such as increasing farmers' income, production quality, and environmental concerns need to be addressed. This study aims to explore strategies for sustainable development of the coffee industry, as well as provide recommendations to improve farmers' welfare and local economic growth.